PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF MENGGUNAKAN CANVA PADA MATA PELAJARAN IPAS DI KELAS IV SD N 11 KOTO BARU - Wiwik Okta Susilawati; M. Anggrayni; Anisa Fitri Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study develops learning media in the form of interactive learning videos using Canva research development. type of development research or in English Research and Development (R&D) based on the validation test results of 4 validators, the validation results carried out by the validator were categorized as very valid with an average of 92.95 categories, namely: language validation received a very valid category with a percentage of 97.5 %, the media category gets a very valid category with a percentage of 96%, the material category gets 93.3% with a very valid category, the practicality assessment is filled in by educators with a percentage of 94% categorized as very practical and students get a percentage of 91.65% with a very practical category Practically, the effectiveness assessment looks at the learning outcomes of students who have experienced an increase, obtaining a percentage of 95.4% in the very effective category.